Awareness on Application of Antacids among Undergraduate Students - Ranjana V1 , Keerthi Sasanka2 , R Gayathri3 , Visalakshi Ramanadhan4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Antacids are usually a class of medication that neutralize stomach acidity and makes its pH more neutral.Commonly used self prescribed medications. Antacids usually consist of magnesium, calcium carbonateand aluminium salts in various compounds or in combination. Gastric acid related disorder could be treatedusing antacids.Ingestion of antacids must be followed only after ingestion of Meals. The main aim of thesurvey was to create awareness on application of antacids among undergraduate students. A questionnairewas prepared and administered to 100 participants through an online Google forms link. Study participantsincluded undergraduate students of 18- 26 age group. Method of representation of each output variable wasin pie chart form. The result was then statistically analyzed using SPSS software. The result was analyzedas 64% were aware on the application of antacids. 55% think antacids are only used to neutralize acidity butother research shows it can reduce activity of pepsin. 45% feel common side effects of overusing antacidsare constipation, Diarrhea, Kidney stones. It shows that severe side effects are rare, although they can occurin high-risk patients. But minor problems like change in bowel habits can occur frequently. This studyconcludes that antacids have a high neutralizing capacity and give relief and comfort. Also inactivate Pepsinto relieve symptoms and provide temporary relief and comfort. Natural foods like mint, milk, Banana,ginger can be taken instead of antacids.